2007
DOI: 10.1111/j.1365-246x.2007.03369.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring overburden layer changes and fault movements from time-lapse seismic data on the Valhall Field

Abstract: S U M M A R YA method developed by Røste et al., which discriminates between layer thickness and velocity changes, is tested on pre-stack time-lapse seismic ocean bottom cable (OBC) data from the Valhall Field. A key parameter in this discrimination process is the dilation factor, α, which is the relative velocity change divided by the relative thickness change within a given layer. The high quality and good repeatability of the OBC data enables us to estimate α with a reasonable accuracy for α-values between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…Several datasets have shown that time‐shifts may, or may not, vary with offset or azimuth (e.g. Røste, Landrø and Hatchell ; Hawkins ; Kudarova et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Several datasets have shown that time‐shifts may, or may not, vary with offset or azimuth (e.g. Røste, Landrø and Hatchell ; Hawkins ; Kudarova et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…The 4D images produced with the LoFS data provide a structural framework for identifying undrained areas, managing existing wells, and analyzing geohazard potentials (Røste al., 2007;van Gestel et al, 2008). Integrated with reservoir modeling, LoFS system reduces the uncertainties in reservoir performance predictions (van Gestel et al, 2011).…”
Section: Time-lapse Fwi On Valhallmentioning
confidence: 99%
“…For example, recent studies highlight the role of pressure changes and associated deformation in observed time-lapse seismic anomalies below, within, and above a producing reservoir (Guilbot & Smith 2002;Landro & Stammeijer 2004;Hatchell & Bourne 2005;Tura et al 2005;Hawkins et al 2007;Hodgson et al 2007;Rickett et al 2007;Roste et al 2007;Schutjens et al 2007;Staples et al 2007). These studies document both changes in layer position and thickness as well as seismic velocity changes due to stress variations.…”
Section: Introductionmentioning
confidence: 97%